THE CORRECTION OF THE SPINAL COLUMN DEVIATIONS FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS FROM SECONDARY SCHOOL - Maria-Daniela; Ágnes SIMON-UGRON; Andreea Raluca TOHAT (Cluj University Press, 2015)
Introduction: The correction of the spinal column deviations for children with special educational needs is an important aspect, especially in the context of the current tendency of social inclusion for this category of people. A correct posture represents the "cornerstone" for a healthy lifestyle, and this implies paying more attention to physical exercises, alimentation and the balance between work and rest. Material and methods: The research had been done on a group of six students with special educational needs from "Special number 2 secondary school" from Baia Mare and it was held between 15.11.2013 and 30.04.2014. The recovery programs include both simple and complex exercises, with a higher level of difficulty. Having in mind the special features of the subjects, the recovery period was parted in three stages. Results: The improvement of the rig cage mobility in the final evaluation was visible for every participant. Regarding the abdominal perimeter when it comes to inhaling and exhaling, the improvements had been up to 1cm in the final evaluation for most cases. After testing the mobility by measuring the distance between the fingers and the ground in the final evaluation, the results had improved significantly for most subjects. Conclusion: The improvement of the respiratory capacity is demonstrated through the progress regarding the rib cage mobility, the abdominal perimeter and the torso for all the participants from the recovery program. The amelioration of articular mobility is also confirmed by the results obtained after having applied the specific tests. Corectarea deviaţiilor coloanei vertebrale la elevii cu cerinţe educative speciale din ciclul gimnazial. Introducere: Corectarea deviaţiilor coloanei vertebrale la elevii cu cerinţe educative speciale reprezintă un aspect important, mai ales în contextul tendinţei actuale de incluziune socială al acestei categorii de persoane. O postură corectă reprezintă "piatra de temelie" pentru un stil de viaţă sănătos, iar acest lucru implică acordarea unei atenţii deosebite exerciţiilor fizice, alimentaţiei şi echilibrului dintre muncă şi repaus Material şi metode: Cercetarea a fost realizată pe un grup de 6 elevi cu cerinţe educative speciale de la "Şcoala gimnazială specială numărul 2" din Baia Mare şi s-a desfăşurat în perioada 15.11.2013 - 30.04.2014. Programele de recuperare conţin atât exerciţii simple cât şi exerciţii complexe, cu un grad mai ridicat de dificultate. Având în vedere particularităţile subiecţilor, perioada de recuperare a fost împărţită în 3 etape. Rezultate: Îmbunătăţirea mobilităţii cutiei toracice în cadrul evaluării finale este evidentă la toţi participanţii. În ceea ce priveşte modificarea perimetrului abdominal în inspir şi expir maxim, se poate observa o îmbunătăţire cu 1cm în cadrul evaluărilor finale în majoritatea cazurilor. În urma aplicării testului de mobilitate reprezentat de distanţa degete-sol din etapa finală a cercetării, se pot observa cele mai semnificative îmbunătăţiri la majoritatea subiecţilor. Concluzii: Îmbunătăţirea capacităţii respiratorii este demonstrată prin progresele obţinute în ceea ce priveşte mobilitatea cutiei toracice, perimetrul abdominal şi bustul în rândul tuturor participanţilor la programul de recuperare desfăşurat. Ameliorarea mobilităţii articulare este confirmată de rezultatele obţinute în urma aplicării testelor specifice. Cuvinte cheie: cerinţe educative, corectare, mobilitate.